2016
DOI: 10.1111/jphd.12193
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with oral health‐related quality of life among safety‐net clinic patients

Abstract: An intervention to remedy dental neglect is recommended to improve OHRQoL among uninsured safety-net patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…A previous study showed the link between less restricted sugar consumption and poorer OHRQOL held up in the multivariate analysis controlling for oral health status, suggesting that the students take account of preventive behaviours when judging their OHRQOL, irrespective of their oral disease status 20. Adopting preventive oral health behaviours in daily life, such as brushing teeth twice a day,21 flossing after meals22 and a healthy diet,21 23 has also become an economical and indispensable way to improve OHRQOL even in the absence of oral disease. Some studies of children aged about 9–15 years showed that supervised toothbrushing24 25 and flossing daily26 were effective in the prevention of gingivitis, while gingivitis was found to be negatively associated with children’s OHRQOL 27.…”
Section: Introductionmentioning
confidence: 91%
“…A previous study showed the link between less restricted sugar consumption and poorer OHRQOL held up in the multivariate analysis controlling for oral health status, suggesting that the students take account of preventive behaviours when judging their OHRQOL, irrespective of their oral disease status 20. Adopting preventive oral health behaviours in daily life, such as brushing teeth twice a day,21 flossing after meals22 and a healthy diet,21 23 has also become an economical and indispensable way to improve OHRQOL even in the absence of oral disease. Some studies of children aged about 9–15 years showed that supervised toothbrushing24 25 and flossing daily26 were effective in the prevention of gingivitis, while gingivitis was found to be negatively associated with children’s OHRQOL 27.…”
Section: Introductionmentioning
confidence: 91%
“…The individual factors that go in favor of our research hypothesis are education level (p = 0.025, ɳ² = 0.05), number of daily brewing (p = 0.01, ɳ² = 0.077) and age class (p = 0.021, ɳ² = 0.074). Kamimura et al in 2017 also show a significant influence (p < 0.01) of the number of daily tooth brushing on oral health related quality of life[19]. Khosrozadeh et al on their part identify the influence of educational level (p < 0.001), number of daily tooth brushing (p < 0.0001) and age (r = -0.353, p = 0.0001) on oral health related quality of life[13].…”
mentioning
confidence: 91%